Model Development of Tax Accounting With Tax Computer Program - Jasman Saripuddin Hsb, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Model Development of Tax Accounting With Tax Computer Program